2018
DOI: 10.3390/ijerph16010091
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Social Support Received by Informal Caregivers: A Personal Network Analysis Approach

Abstract: Social support is an important predictor of the health of a population. Few studies have analyzed the influence of caregivers’ personal networks from a gender perspective. The aim of this study was to analyze the composition, structure, and function of informal caregiver support networks and to examine gender differences. It also aimed to explore the association between different network characteristics and self-perceived health among caregivers. We performed a social network analysis study using a convenience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 36 publications
6
36
0
2
Order By: Relevance
“…Informal male and female caregivers also differ in their main coping mechanisms [ 42 ]. Males tend to use more active stress-management mechanisms, such as those based on substance use, while females tend to rely on more passive mechanisms based on praying and hoping for the best.…”
Section: Discussionmentioning
confidence: 99%
“…Informal male and female caregivers also differ in their main coping mechanisms [ 42 ]. Males tend to use more active stress-management mechanisms, such as those based on substance use, while females tend to rely on more passive mechanisms based on praying and hoping for the best.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, it has been observed that women and male caregivers receive different support from the family, with, once again, women receiving less family support, while male caregivers receive more collaboration. (35) In addition to the consequences on health, time and family relationships, in the area of professional and paid work-life, known as the produc-tive sphere, (37) there are also important effects. Among the economic consequences are: not being able to work outside the home, having had to leave work or to reduce working hours, having problems at work due to difficulties in meeting schedules or not being able to go to work in emergencies.…”
Section: Gender Perspectivementioning
confidence: 99%
“…Social support has been studied in several contexts, one of which is informal caregiving [27,28]. Compared to other approaches in social support research, personal network analysis (PNA), also labeled as egocentric network analysis in the literature [29], is based on the ensemble of relationships that surround an individual (ego) across social settings (i.e., family, work colleagues, neighbors, .…”
Section: Introductionmentioning
confidence: 99%